Comprehensive evaluation of different strategies to recover methanogenic performance in ammonia-stressed reactors. (September 2021) - Yan, Miao; Zhu, Xinyu; Treu, Laura; Ravenni, Giulia; Campanaro, Stefano; Goonesekera, Estelle Maria; Ferrigno, Rosa; Jacobsen, Carsten S.; Zervas, Athanasios; Angelidaki, Irini; Fotidis, Ioannis A.
Graphical abstract: Highlights: Bioaugmentation with ready-to-use inocula was demonstrated for the first time. Bioaugmentation with gel-preserved consortium raised the Rmax by 77%. Wood biochar raised the Rmax by 35%. Straw biochar induced selective raise of M. thermophila under ammonia stress. Woodchip biochar possibly contributed to interspecies Direct Electron Transfer. Abstract: In this study, strategies for recovery of ammonia-stressed AD reactors were attempted, by addition of preserved bioaugmentation consortium in gel (BioG), fresh consortium in liquid medium (BioL), woodchip biochar (BW), and straw biochar (BS). In comparison to control group with ammonia, effective treatments, i.e., BioG, BioL, BW and BS raised the maximum methane production rate by 77%, 23%, 35%, and 24%, respectively. BW possibly acted as interspecies electrical conduits for Direct Electron Transfer based on conductivity and SEM analysis. BioG facilitated slow release of bioaugmentation inocula from gel into the AD system, which protected them from a direct environmental shock. According to microbial analysis, both BioG, BioL and BW resulted in increased relative abundance of Methanothermobacter thermautotrophicus ; and BS induced selective raise of Methanosarcina thermophila . The increase of methanogens via these strategies led to the faster recovery of the AD process.